Question
Simplify for \( x=-1 \) \( 3(x+1)^{2}-3 \)
Ask by Santiago Murphy. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
When \( x = -1 \), the expression \( 3(x+1)^{2} - 3 \) simplifies to \(-3\).
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Unlock
Reviewed and approved by the UpStudy tutoring team
Like
Mind Expander
To simplify \( 3(x+1)^{2}-3 \) for \( x=-1 \), first substitute \(-1\) into the expression. Starting with \( x+1 \): \[ x + 1 = -1 + 1 = 0 \] Now substitute \( 0 \) into the expression: \[ 3(0)^{2} - 3 = 3(0) - 3 = -3 \] Thus, the simplified expression for \( x=-1 \) is: \[ -3 \]